The Morphological Variation of the Soft Palate in Hospital Visiting Patients - Dahal, Samarika; Gupta, Sanjay Prasad; Singh, Ashutosh Kumar; Baral, Radha; Srikant N; Giri, Abhishek (Journal of Nepal Health Research Council, 2022)
Background: The soft palate anatomy of individuals can have a range of morphologies. Cephalometric analysis is a low-cost approach to analyze the soft palate in patients with or without developmental abnormalities. Methods: The lateral cephalogram of the patients visiting Tribhuvan University Teaching Hospital, Institute of Medicine for various dental treatment purposes was evaluated. The soft palate was delineated on the radiographs by sketching the soft palate’s contour along its radiolucent outline using the curve lines and connectors of Microsoft PowerPoint. The soft palate was then categorized according to the study by You M et al. Results: The different types of soft palate morphology observed in the study were rat tail (42.4%), leaf-like (40.8%), butt-like shape (8.9%), straight-line (4.7%), s-shaped (1.9%), and crooked (0.9%). The males had rat-tail (44.4%), leaf-like (41.1%), butt-like shape (8.4%), straight-line (3.9%), s-shaped (1.3%), and crooked (0.6%), whereas the females had rat-tail like (40.6%), leaf-like (40.6%), butt-like shape (9.5%), straight-line (5.6%), s-shaped (2.5%), and crooked (1.2%) types of soft palate. Conclusions: The rat-tail form of the soft palate was the most prevalent, followed by the leaf-like in both sexes. The least common type was the crooked form. This study found no evidence of sexual dimorphism. Keywords: Cephalogram; morphology; Nepalese population; soft palate.